Plan de negocios para la creación de gimnasios especializados en tratamientos corporales y cirugía estéticas en la ciudad de Quito - Anangonó Cuamacas, Yadira Vanessa (2019)
The objective of this paper is to seek the viability of the business plan, seeking to provide a complete service for aesthetics, guided by current social trends. The gym focuses on knowing how to treat patients who have undergone body treatments or aesthetic surgeries in the sports field, so the knowledge of the aesthetic part should also be handled by the coaches in order to lock the parts in which there was an intervention and thus obtain greater results and be able to offer a more specialized service since when performing physical activity after having an outpatient aesthetic intervention or body treatment, it is not in the same way that a woman without doing it exercises normally.